The Effect of Depression on Pain Perception and Function in the Foot and Ankle Patient. Issue 3 (14th September 2018) - Alejandro, Shannon; Geswell, Matthew; Grandizio, Louis; Graham, Jove; Cush, Gerard
Category: Other Introduction/Purpose: Foot and ankle (FA) pain can be found in up to 20% of the adult population.1 Etiologies are multifactorial and include neurologic injury, trauma, deformity, tendinopathies and psychological factors. The purpose of this investigation is to assess psychological factors contributing to FA pain in surgical and nonsurgical patients. By identifying how psychological factors influence patient reported pain and disability, clinicians may be able to develop interventions to decrease catastrophic thinking and improve psychological well-being prior to considering surgical intervention Methods: All patients seen in a FA clinic by a single fellowship trained orthopaedic surgeon from August 2016 to October 2016 were included. All patients completed 5 functional assessments prior to their visit (PHQ-2, VAS Pain Scale, FAAM, PSEQ, PCS). We divided the patients into two groups based on their performance on the PHQ (PHQ < 3, or PHQ = 3), which measures depression. Scores = 3 are indicative of clinical depression. Nonparametric Wilcoxon testing was used to determine whether the distributions of the other scores (VAS Pain Scale, FAAM, PSEQ and PCS) were significantly different between these two groups. Results: Of the 225 patients included in our analysis, there were 175 (88%) had PHQ-2 depression scores of < 3 (Group 1) and 50 (22%) had scores = 3 (Group 2). Group 2 demonstrated a statistically significant increase in VAS Pain Scale and PCS. In addition, patients in Group 2 showed statistically significant decreases in FAAM and PSEQ. Patients in Group 2 were statistically more likely to be obese, use tobacco, and be unemployed. Conclusion: In patients with common FA complaints, those with clinical depression, as assessed by the PHQ-2, demonstrated increased pain scores, decreased ability to cope with pain, and lower functional outcome scores compared to patients without depression. Tobacco use, obesity and employment status were found to independently affect pain, coping, and function of patients. These data suggest that depression can significantly affect a patient's ability to cope with pain and to achieve a higher functional outcome. This data suggests patients with depression may have increased difficulty coping with their FA ailment leading to the need for increased counseling regarding expected outcomes.